A NEW ARTIFICIAL INTELLIGENCE MODEL FOR AIR QUALITY PREDICTION AND ANALYSIS - Ms.VALAPALA PRABHAVATHI G.SAHITHI,G.AKHILA, K.SAHASRA,G.MANUSHA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Traffic and power generation are the main sources of urban air pollution. The idea that outdoor air pollution can cause exacerbations of pre-existing asthma is supported by an evidence base that has been accumulating for several decades, with several studies suggesting a contribution to new-onset asthma as well. In this Series paper, we discuss the effects of particulate matter (PM), gaseous pollutants (ozone, nitrogen dioxide, and sulphur dioxide), and mixed traffic-related air pollution. We focus on clinical studies, both epidemiological and experimental, published in the previous 5 years. From a mechanistic perspective, air pollutants probably cause oxidative injury to the airways, leading to inflammation, remodelling, and increased risk of sensitisation. Although several pollutants have been linked to new-onset asthma, the strength of the evidence is variable. We also discuss clinical implications, policy issues, and research gaps relevant to air pollution and asthma.